Why Does Education Reduce Crime? - Brian Bell; Rui Costa; Stephen Machin (Institute of Labor Economics (IZA), 2018)
Prior research shows reduced criminality to be a beneficial consequence of education policies that raise the school leaving age. This paper studies how crime reductions occurred in a sequence of state-level dropout age reforms enacted between 1980 and 2010 in the United States. These reforms changed the shape of crime-age profiles, reflecting both a temporary incapacitation effect and a more sustained, longer run crime reducing effect. In contrast to the previous research looking at earlier US education reforms, crime reduction does not arise solely as a result of education improvements, and so the observed longer run effect is interpreted as dynamic incapacitation. Additional evidence based on longitudinal data combined with an education reform from a different setting in Australia corroborates the finding of dynamic incapacitation underpinning education policy-induced crime reduction.
Keywords: I2; K42; 330; crime age profiles; school dropout; compulsory schooling laws